Additions to Cercospora from North-Eastern Uttar Pradesh - A.N. SINGH and NISHA KUMARI, H.D. BHARTIYA, SATYA NARAYAN, (Indian Phytopathology, 2003)
Four new species of Cercospora Viz., C. atylosigena, C. celosiicola, C. moghamicola and C. pouzolziicola, occurring on Atylosia sp., Celosia coronata, Moghamia prostrata and Pouzolzia indica, respectively are described and illustrated.